Matizes do mal-estar dos professores: um estudo de caso de uma escola pública do ensino médio. - Jussara Bueno de Queiroz Paschoalino (2007)
The objective of this study was the investigation of the teachers' of the Medium Teaching educational indisposition in municipal network school of Belo Horizonte. The choice of the qualitative research of the type case study was an option that made possible to discovery curtain evidences of the singularity of the construction of the identity of that school. For us to develop this study we used the observation techniques, of semi-structured interviews, of the documental analysis and of questionnaires. In the done investigation it was necessary to retract the teacher at the present time in the complexity of your work. The entimema that to be a teacher it is to be suffer, it was an important die in the research, revealing that the challenges, the impositions and the changes in the educational field left the teacher of the school researched without foundation to accomplish your work. In that sense, the results of the research show multiples bad feelings, permeating the researched school, through manifestations evidenced in several dimensions: the indisposition of the losses, the indisposition of the relationships of disputes starting from the processes of direction eligibility and coordinators, the indisposition of the teachers' silent, indisposition of the blame, of the absenteeism and of the presenteeism. Finally, we verified that the teacher was shown suffered, manifesting the sharpness of your indisposition in reactions that mark your body and your psychic one for the illness. The relevance of the analyses done of this dissertation it expressed, above all, in the evidences of the existence of the educational indisposition, because the desire existed of being different, of being recognized, of being a teacher capable to contribute for the youths' formation and for the society.